Fully Patterned Low‐Voltage Transparent Metal Oxide Transistors Deposited Solely by Chemical Spray Pyrolysis. (17th January 2013) - Faber, Hendrik; Butz, Benjamin; Dieker, Christel; Spiecker, Erdmann; Halik, Marcus
Abstract All‐inorganic transparent thin‐film transistors deposited solely by the solution processing method of spray pyrolysis are reported. Different precursor materials are employed to create conducting and semiconducting species of ZnO acting as electrodes and active channel material, respectively, as well as zirconium oxide as gate dielectric layer. Additionally, a simple stencil mask system provides sufficient resolution to realize the necessary geometric patterns. As a result, fully functional low‐voltage n‐type transistors with a mobility of 0.18 cm2 V−1 s−1 can be demonstrated via a technique that bears the potential for upscaling. A detailed microscopic evaluation of the channel region by electron diffraction, high‐resolution and analytical TEM confirms the layer stacking and provides detailed information on the chemical composition and nanocrystalline nature of the individual layers.